FROM LIKES TO LOVE: A QUALITATIVE STUDY OF SOCIAL MEDIA CONTENT AND THE POPULARITY OF TENNIS IN INDONESIA - Kristina, Ritantri (Transpublika Publisher, 2024)
Tennis, once a sport primarily enjoyed by a select group of fans, is experiencing a tremendous resurgence in popularity, especially in Indonesia. This resurgence can be attributed, in part, to the rise of social media content featuring celebrities such as Raffi Ahmad, who has brought tennis back to popularity. This condition can be shown by the difficulty of accessing tennis courts and tennis equipment stores, which many consumers again visit. This article explores qualitative research conducted to understand social media content, tennis popularity, and the experiences and perspectives of current tennis players. This research uses a qualitative approach to gain an in-depth understanding of the study of social media content, the popularity of tennis, and the experiences and perspectives of current tennis players in Indonesia. The primary method used in the study was semi-structured interviews with informants, including tennis players, tennis coaches, tennis supply store staff, and tennis court managers. This study aimed to explore the function of social media on the rise in popularity of tennis and explore the challenges tennis fans face. This study aims to comprehensively understand the qualitative aspects of the rise of tennis popularity in Indonesia through qualitative interview methods. The insights gained through this research are to inform strategies to promote the sport further, improve accessibility, and positively impact the tennis community.